Zero Logic Adding Up to Classical Logic - Batens, Diderik (Logical Studies, 1999)
The present paper presents a logic that allows for the abnormal behaviour of any logical constant and for the ambiguous behaviour of any non-logical constant, but nevertheless offers an interpretation of the premises that is as normal as possible. If the premises have classical models, the logic assigns them the same consequence set as Classical Logic. The semantics of the logic is presented, the dynamic proof theory is hinted at, and some comments are added on the philosophical significance of the result.
(Electronic Journal: {\smallhttp://www.logic.ru/LogStud/02/LS2.html})